2015
DOI: 10.3109/17435390.2015.1038330
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose AgNPs reduce lung mechanical function and innate immune defense in the absence of cellular toxicity

Abstract: Multiple studies have examined the direct cellular toxicity of silver nanoparticles (AgNPs). However, the lung is a complex biological system with multiple cell types and a lipid-rich surface fluid; therefore, organ level responses may not depend on direct cellular toxicity. We hypothesized that interaction with the lung lining is a critical determinant of organ level responses. Here, we have examined the effects of low dose intratracheal instillation of AgNPs (0.05 µg/g body weight) 20 and 110nm diameter in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…Additional characteristics of AgNP with gold core are discussed elsewhere by Botelho et al . [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional characteristics of AgNP with gold core are discussed elsewhere by Botelho et al . [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usually, metal NPs are stabilized by a “capping-agent” such as citrate or polyvinylpyrrolidone (PVP) (Bakshi et al, 2008 ; Leo et al, 2013 ). We have demonstrated previously that citrate-stabilized AgNPs elicit little biological response acutely in comparison to PVP-stabilized counterparts (Botelho et al, 2015 ). In this current study we use CB as a control for metal effects.…”
Section: Introductionmentioning
confidence: 91%
“…Our previous in vivo studies examining organ level toxicology of AgNPs (with gold cores) have demonstrated both size- and stabilization-dependent lung function effects (Botelho et al, 2015 ). Usually, metal NPs are stabilized by a “capping-agent” such as citrate or polyvinylpyrrolidone (PVP) (Bakshi et al, 2008 ; Leo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…AgNP studies in Sprague-Dawley (SD) rats provide additional evidence that size may also modify the timing of the inflammatory response and that size and coating affect the quantity and localization of AgNPs (17)(18)(19)(20). Furthermore, in C57BL/6 mice, size modified the dose response and timing of citrate-coated AgNP-induced lung inflammation, and surface coating and size altered AgNP effects on lung surfactant proteins and lung mechanics after instillation (10,21).…”
mentioning
confidence: 99%
“…Additional strain differences included significant increases relative to control in total BALF protein and bronchial hyper-responsiveness in BN rats compared with SD rats after exposure to 20-nm citrate-and PVP-coated AgNPs. Thus, in vivo studies indicate that particle size, coating, and animal strain influence AgNP-induced lung inflammation and toxicity (10,12,(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%